Pre-and post-surgical antibiotic protocol for third molars - Anampa Paucar, Marian Antonia (2022)
Surgical treatment of third molars frequently requires a prophylactic antibiotic protocol and pharmacological treatment after surgery. Analyzing these protocols was the objective of this study. For this, electronic searches were carried out in the main databases (PubMed, SciELO, Science and academic institutional repositories of different universities) in which trials, systematic reviews, meta-analyzes, theses and studies of different types were identified. The search was filtered between the period 2016 to 2021 and it was determined that antibiotics such as amoxicillin, amoxicillin/clavulanic acid, are the prophylactic antibiotics of first choice since they stand out for different properties, among them, a significant reduction in the risk of infection (up to a 99.9 %). The purpose of prophylaxis is to prevent the possible development of infectious diseases, as well as to avoid the proliferation and spread of bacteria that can cause these, especially in non-immunocompetent patients.